2018
DOI: 10.3390/pr6040037
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Mechanical Behaviors of Grouted Sand with UF-OA Grouts

Abstract: A detailed understanding of the engineering properties for grouted sand is a key concern in foundation engineering projects containing sand layers. In this research, experiments of grouting with various grain sizes of sand specimens using a new type of improved chemical material-urea formaldehyde resin mixed with oxalate curing agent (UF-OA), which has rarely been used as grout in the reinforcement of soft foundations, were conducted on the basis of a self-developed grouting test system. After grouting tests, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…For evaluating the flow behavior through the rock fractures, using the Reynolds number (Re) (ratio of inertial forces to viscous forces) to quantify the onset of nonlinear flow: Re = ρQ/µw (6) In order to analyze nonlinear flow behavior through the fracture, T 0 and T were introduced in the research [37], in which the Forchheimer formula (Equation (3)) was rewritten:…”
Section: Normalized Transmissivitymentioning
confidence: 99%
See 2 more Smart Citations
“…For evaluating the flow behavior through the rock fractures, using the Reynolds number (Re) (ratio of inertial forces to viscous forces) to quantify the onset of nonlinear flow: Re = ρQ/µw (6) In order to analyze nonlinear flow behavior through the fracture, T 0 and T were introduced in the research [37], in which the Forchheimer formula (Equation (3)) was rewritten:…”
Section: Normalized Transmissivitymentioning
confidence: 99%
“…These figures indicate that the grouts made of ultrafine cement can penetrate into smaller fractures more easily than the other two kinds of cement grouts, because the former contained substantial amounts of tiny cement grains. The ultrafine cement grouts have been widely used in the reinforcement for underground engineering in the past few decades due to its more stable physical and mechanical properties, greater range of strength adjustability, and better permeability, as well as non-polluting nature [48]. Therefore, the ultrafine cement grouts with W/C ratios of 0.8, 1.0, 1.2, 1.5, and 2.0 were selected in the experiment.…”
Section: Grout Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Related studies have found that the particle size of sand has a great effect on the strength of cemented similar materials [18,19]. Some studies consider that the increase of small sand particles can improve the mechanical properties of cementitious materials to a certain extent [20,21]. Jinxiao Jia believed that the smaller the particle size is, the fewer defects on the surface, so the mechanical strength increases with decreasing particle size [22]; On the contrary, Haifei Lin found that the larger the sand size is, the larger the contact area between the sand particles is.…”
Section: Introductionmentioning
confidence: 99%
“…Fractured rock masses (Figure 1(a)) are widely distributed in underground engineering due to geological action or excavation disturbance, which may bring serious safety hazard to the engineering stability [1][2][3][4]. Grouting is a useful way for controlling groundwater inrush and improving mechanical properties of fractured rocks in underground mining and engineering [5][6][7][8][9]. In order to acquire a better understanding of the grouting mechanism of fractured rock, lots of experimental studies have been performed in recent decades.…”
Section: Introductionmentioning
confidence: 99%